Three essays on foreign direct investment - Kukeli, Agim, author; Fan, Liang-Shing, advisor; Dalsted, Norman L., committee member; Kling, Robert, committee member; Fan, Chuen-mei, committee member (Colorado State University. Libraries, 2004)
This dissertation examines, from both microeconomic and macroeconomic perspectives, foreign direct investment in general and especially in Central and Eastern European countries that experienced the transformation of their economies from central planning to market oriented system. The dissertation is organized in the form of three essays treating three different topics on international production. Essay one, a game theory application, examines the strategic behavior of firms when they decide to enter a new market (possibly abroad) and exercise the real option under demand uncertainty as well as uncertainty about the strategic behavior of its competitor. Equilibrium has been derived showing that while firms play pure strategies on quantities of product they produce, they randomize their strategic behavior. In addition, the probability of entry into a foreign market has been derived using a mixed strategy equilibrium concept. Essay two examines the role of institutional progress and economic policy performance in transition economies and their effect on the foreign direct investment inflow within these countries. A double log econometric model using Seemingly Unrelated Regression technique estimated that, in addition to economic policies aiming to control inflation, maintaining a stable economic situation in the country, political stability and civil liberties by in large drive foreign capital inflow. Essay three is primarily concerned with the effect of foreign capital inflow (both as a physical capital and as a technology transfer) in the economic growth in the transition economies as measured by the rate of growth of gross domestic product. A semi-log econometric model has been estimated to evaluate the impact of foreign direct investment on the growth rate of gross domestic output. In addition, these effects have been estimated for different "modes of transition": namely for "shock therapy" and "gradualism".
Keywords: essays; game theory; decision making